OBSTRUCTIVE SLEEP APNEA, SLEEP FRAGMENTATION AND CARDIOVASCULAR AUTONOMIC DYSFUNCTION: MECHANISMS AND CLINICAL IMPLICATIONS - Antonina Broen , Julia; Koperdowska, Julia (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder associated with significant cardiovascular morbidity. Recurrent upper airway obstruction during sleep leads to intermittent hypoxia and repeated arousals, resulting in sleep fragmentation (SF). Increasing evidence suggests that both processes contribute to dysregulation of the autonomic nervous system and adverse cardiovascular outcomes. Methods: A narrative literature review was conducted using PubMed and Google Scholar to identify relevant studies published up to 1 March 2026. The search strategy combined Medical Subject Headings (MeSH) and free-text terms related to sleep fragmentation, obstructive sleep apnea, autonomic dysfunction, and cardiovascular outcomes. Eligible studies included randomized controlled trials, cohort studies, systematic reviews, meta-analyses, and clinical guidelines involving adult populations. Results: Recurrent microarousals from sleep fragmentation disrupt sleep continuity and increase sympathetic activity, manifesting as altered heart rate variability and sympathetic dominance. Sleep fragmentation alone can destabilize autonomic regulation independently of hypoxia. In obstructive sleep apnea, intermittent hypoxia adds oxidative stress and hypothalamic-pituitary-adrenal axis activation. Persistent sympathetic overactivity causes hemodynamic instability, impaired nocturnal blood pressure dipping, vascular stiffness, and cardiac remodeling, raising the risk of hypertension, arrhythmias, heart failure, and other cardiovascular events. Conclusions: Sleep fragmentation and intermittent hypoxia are central mechanisms linking obstructive sleep apnea to cardiovascular autonomic dysfunction. They drive sustained sympathetic activation and progressive cardiovascular damage, highlighting the need for comprehensive diagnosis and therapies targeting both apnea reduction and improvements in sleep continuity and autonomic balance.